(untitled) (The Lumbini Journal of Business and Economics, 2026)
Purpose: This study examines the impact of integrated Human Resource Management (HRM) systems on the performance of organization in emerging economy banking as there is a paucity of empirical research on integrated HRM bundles as opposed to individual practice. Methods: The current research has a cross-sectional design based on quantitative research and a sample of 211 employees of six commercial banks in Nepal and the PLS-SEM is used. The HRM practices are delineated as interconnected aspects of an integrated HRM system (bundle), and are also described as separate latent constructs, so that the individual and interactive impacts on organizational performance can be measured. Results: Findings prove compensation and reward, (beta = 0.264, p < 0.01) performance appraisal, (beta = 0.259, p < 0.01) and training and development significantly increase organizational performance. In contrast, recruitment and selection does not show a significant direct effect, suggesting that there is little differentiation of performance in the hiring stage. Conclusion: The theoretical contribution made by organizational performance in the banking sector is that the capability development and performance alignment of the employees and motivational mechanisms is the dominant source of performance compared to the initial hiring practices in the banking sector, which in turn theoretically contributes to the integrated HRM-performance framework and practically guides the banks towards focusing on training, appraisal and performance-based rewards.